Work ethics climate in relation to nurses’ commitment in a South African hospital - Mahlamakiti D. Kau; Jeremy Mitonga-Monga; Tebogo K. Molotsi (SA Journal of Human Resource Management, 2024)
Orientation: Commitment, well-being and employer loyalty affect nurse retention. Literature shows that nurses are leaving the workforce at an alarming rate and that various factors are causing them to leave their employers.